Medicare and Accounting. - Buckley, John W. (The Accounting Review, 1966)
The accounting requirements of Medicare are more rigorous than appears obvious on the surface. Many of the providers, particularly in the nursing home sector, lack adequate accounting systems in the present circumstances–without the added requirements of Medicare. Many of these institutions will find it necessary to convert from their present cash method of accounting to an accrual basis that includes a costing, standard costing, and periodic reporting capability. The resources of the individual institutions, monetarily and technically, are insufficient to cope with the changes that are needed. The intermediaries recognized in Public Law 89-97 will be able to provide some of the assistance these institutions need to meet their new accounting requirements. But there is also an opportunity for the accounting profession to make a valuable contribution to sound accounting practice in this field of interest by sponsoring institutes, offering courses in institutional accounting, and establishing and maintaining the necessary accounting systems through consultation and the audit function.